The intimate scene in a remote university research and extension project (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
The notions of immersion theatre, intimate scene, neo-technological theater and audio-theater permeate a path in research and university extension that started before, but continued during the Covid-19 pandemic. The intimate scene is a scenic format that favors the encounter, sensory immersion and processes of disorientation regarding space, time and presence. The measures of social isolation and the implementation of remote emergency academic activities led to a specific context of creative experimentation, in which elements of the intimate scenic format were reinterpreted based on the limitations and potential of telematic and virtual presences. Despite the distinctions between theatrical experiences (in person) and remote artistic experiences, technological mediations are adopted in this project as devices to imagine a possible remote intimate scene and produce multiple records of the creative process.
Keywords: Immersion theater; Intimate scene; Remote creative process; University outreach